The closer [large type] : [my story] - Rivera, Mariano, 1969- (Little Brown & Co., 2014)
Mariano Rivera tells his story for the first time: the championships, the bosses (including the Boss), the rivalries, the struggles of being a Latino baseball player in the United States, and of maintaining Christian values in professional athletics. The twelve-time All-Star will discuss what it's like to run up to that mound with the game, or the season squarely on his shoulders.